2022
DOI: 10.1021/jacs.2c08827
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Inverse Design for 2D Ferroelectric Rashba Semiconductors

Abstract: A long-standing goal in spintronics is electric control of spin. Herein, we perform an inverse design to search for 2D ferroelectric Rashba semiconductors, whose spin texture can be precisely and readily reversed by switching ferroelectric polarization via the electric field. The inverse design involves defining and utilizing the design principles of the Rashba effect and ferroelectricity. After screening materials from a database based on the enabling design principles, we identify three potential types of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…The value of the Rashba coefficient of those compounds is in the range of 1.28-1.87 eV Å, which is much larger than the Janus transition metal dichalcogenide and other 2D materials. [69][70][71]…”
Section: Electronic and Optical Propertiesmentioning
confidence: 99%
“…The value of the Rashba coefficient of those compounds is in the range of 1.28-1.87 eV Å, which is much larger than the Janus transition metal dichalcogenide and other 2D materials. [69][70][71]…”
Section: Electronic and Optical Propertiesmentioning
confidence: 99%
“…[12,13] This remarkable property is singular to this class of multifunctional materials and is sought-after for spintronic applications such as spin field effect transistors, non-volatile and bipolar mem ories as well as programmable transistors for nematics and logic operations. [8,[13][14][15][16] The development of FERSC demands materials exhibiting ferroelectricity, semiconductor properties and a sizeable Rashba effect at the same time. Recent theoretical studies have suggested a number of potential FERSC candidates like complex oxides, [17][18][19] perovskites [20][21][22] or 2D materials, [15,23,24] but so far, FERSC have been demonstrated experimentally only for the IV-VI class of semiconductors (see Figure 1b).…”
Section: Ferroelectricmentioning
confidence: 99%
“…This means that in a FERSC the spin polarization can be externally controlled and reversed by an applied electric field via a non-volatile and switchable poling process [12,13] . This remarkable property is singular to this class of multifunctional materials and is sought-after for spintronic applications such as spin field effect transistors, non-volatile and bipolar memories as well as programmable transistors for nematics and logic operations [9,[13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The development of FERSC demands materials exhibiting ferroelectricity, semiconductor properties and a sizeable Rashba at the same time. Recent theoretical studies have suggested a number of potential FERSC candidates like complex oxides [17][18][19] , perovskites [20][21][22] or 2D materials [15,23,24] , but so far, FERSC have been demonstrated experimentally only for the IV-VI class of semiconductors (see Fig. 1(b)).…”
Section: Introductionmentioning
confidence: 99%